2010
DOI: 10.1093/cercor/bhq224
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Cerebral Metabolic Rate and Blood Supply across the Adult Lifespan

Abstract: With age, the brain undergoes comprehensive changes in its function and physiology. Cerebral metabolism and blood supply are among the key physiologic processes supporting the daily function of the brain and may play an important role in age-related cognitive decline. Using MRI, it is now possible to make quantitative assessment of these parameters in a noninvasive manner. In the present study, we concurrently measured cerebral metabolic rate of oxygen (CMRO(2)), cerebral blood flow (CBF), and venous blood oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
351
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 331 publications
(416 citation statements)
references
References 60 publications
61
351
4
Order By: Relevance
“…In terms of WM rCBF, one did not observe any differences in SZ while another observed that WM rCBF decreased with age and faster in SZ (Pinkham et al, 2011;Wright et al, 2014). Similarly, this study found an aging effect of AC WM rCBF, which is also consistent with work showing rCBF decrease across life span (Lu et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…In terms of WM rCBF, one did not observe any differences in SZ while another observed that WM rCBF decreased with age and faster in SZ (Pinkham et al, 2011;Wright et al, 2014). Similarly, this study found an aging effect of AC WM rCBF, which is also consistent with work showing rCBF decrease across life span (Lu et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Finally, GM CVR in elderly was significantly lower (Po0.001) than that in young, which is relatively well established from the previous literature. 36,37 Further analysis was performed to test the possibility that the WM time course is best matched by the convolution of the GM time course with an exponential dispersion function, rather than by simply shifting the GM time course. The optimal time constant for the exponential function was found to be 26 ± 5 and 8±2 seconds for younger and older subjects, respectively, with a significant group difference (P ¼ 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to emphasize that lower baseline CBF does not mean lower brain metabolism (oxygen or glucose) in the context of aging. In fact, recent literature suggested that baseline brain oxygen metabolic rate is greater in the older individuals (Lu et al 2011), presumably related to lower efficiency in mitochondria and neuronal functions. This concomitant increase in metabolic demand and decrease in blood supply of course will result in a higher oxygen extraction fraction (OEF) with age, which has been confirmed as well (Lu et al 2011).…”
Section: Discussionmentioning
confidence: 99%